Parahyangan Catholic University Relationship Management Pilot Project At FISIP-UNPAR - Agus Gunawan (Jurnal Administrasi Bisnis, 2008)
Considering that relations with the students is really important as one of the approachesto get its competitive advantages, a university must knows exactly eachof the students so the university’s staffs can interact, communicate and fulfill thestudents needs personally. In order to maximize the effort, the university must use itsstudents’ database supported with information technology to create customer knowledgecompetence. To make the adequate CRM function with risk management fromthe beginning to reduce the risks which can be came up, the university must havecustomer mapping, employee commitment and re-organization.Keywords: Customer Relationship Management, Knowledge Management, RiskManagement